Bullying dalam Perspektif Nilai Fundamental Tafsir Maqashidi: Analisis Maqasid Syariah Dalam rangka Hifdz Aql Dan Hifdz Nafs - Idris, Idris; Abshor, M Ulil (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2024)
Bullying is a social phenomenon that has a significant negative impact on physical and mental well-being and social harmony. From an Islamic perspective, bullying is contrary to the values of the Shariah, which aims to protect and respect human rights. This research aims to analyse the phenomenon of bullying through a maqashidi interpretive approach that focuses on the maqashid principles of Sharia, specifically hifdz nafs (preservation of the soul) and hifdz aql (preservation of the spirit). This research used a descriptive-analytical method based on desk research, with the main sources being the Qur'an, Hadith, and classical and contemporary tafsir books. The analysis showed that bullying violates the principle of hifdz nafs by threatening the security of the soul and the emotional balance of the individual, as well as the principle of hifdz aql because it hinders the intellectual development and mental health of the victim. This research recommended a Maqasid Sharia values-based approach to preventing and addressing bullying by raising awareness of the importance of upholding honour and human rights. The results of the research are expected to serve as a basis for the development of social, educational and legal policies that prioritise the protection of the soul and intellect, in line with the main objective of Islamic law to create universal benefits.